Investigation of Bioabsorbable Screw Usage for Longbone Fracture Repair in the Horse: Biomechanical Features - Field, J. R.; Hearn, T. C.; Arighi, M. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The purpose of the study was to compare the biomechanical features of bioabsorbable, self-reinforced polyL-lactic acid (SR-PLLA) and stainless steel 4.5 mm ASIF screws. Paired extraction tests were conducted in matched third metacarpal bones and in a synthetic bone material composed of polyurethane foam. The tests were accomplished using a servohydraulic materials testing machine. From these tests the maximum value of tensile force, achieved during extraction, was recorded as the screw “holding strength‘.Comparison of holding strengths in horse cadaver bones revealed a significant difference (p = 0.0002) between screw types. The axial tensile strength of the SR-PLLA screws (878 Newtons) was much lower than that achieved by the ASIF screws (8513 N). Subsequent testing in synthetic material again reflected significant differences (p <0.0001) between the screw types. The results may be accounted for by differences in the thread-to-core ratio between the screw types. Other factors, such as elastic deformation of the bioabsorbable screw, may also contribute through differences in the mechanical interface between screw and media.
Keywords: Bioabsorbable; holding strength; cortical bone screws